HIZMET KALİTESİNİN TÜKETİCİ MEMNUNİYETİ ÜZERİNE ETKİSİ: LYDEC, KASABLANCA'DA MÜŞTERİ HİZMETLERİ İÇİN VAKA ÇALIŞMASI - JAOUHARY, ILHAM (PEARSON JOURNAL, 2021)
Morocco's power sector was considered a natural monopoly of the public sector, but it has since been privatized, rebuilt, and reinvested in by the private sector. The country's energy division, which is usually referred to as backward, under-funded, and unmanaged, experiences losses of approximately 20-20% in 2009-2010. Moroccan authorities assigned LYDEC, a private sector partnership and a subsidiary of SUEZ Environment - a range of water and waste services that are part of SUEZ - to handle Casablanca's energy, water, and sanitation in 1997. The main purpose of the 30-year Agent Management Contract was to provide Casablanca residents with access to essential services (a combination of electricity, water, and wastewater), representing 4.5 million residents). Quantitative research is used for studies and also explains which method is used to collect data. The study methodology relies on the use of data analysis, descriptive analysis, and centralized programming (SPSS). The results show that there is a positive correlation between all the variables. But empathy and trust with people have a highly positive correlation with customer satisfaction